Circadian gene variants in cancer. (June 2014) - Kettner, Nicole M.; Katchy, Chinenye A.; Fu, Loning
Abstract Humans as diurnal beings are active during the day and rest at night. This daily oscillation of behavior and physiology is driven by an endogenous circadian clock not environmental cues. In modern societies, changes in lifestyle have led to a frequent disruption of the endogenous circadian homeostasis leading to increased risk of various diseases including cancer. The clock is operated by the feedback loops of circadian genes and controls daily physiology by coupling cell proliferation and metabolism, DNA damage repair, and apoptosis in peripheral tissues with physical activity, energy homeostasis, immune and neuroendocrine functions at the organismal level. Recent studies have revealed that defects in circadian genes due to targeted gene ablation in animal models or single nucleotide polymorphism, deletion, deregulation and/or epigenetic silencing in humans are closely associated with increased risk of cancer. In addition, disruption of circadian rhythm can disrupt the molecular clock in peripheral tissues in the absence of circadian gene mutations. Circadian disruption has recently been recognized as an independent cancer risk factor. Further study of the mechanism of clock-controlled tumor suppression will have a significant impact on human health by improving the efficiencies of cancer prevention and treatment.